Analysis of the advantages of cis reporters in optimized FACS‐Gal. Issue 7 (4th April 2017) - Sánchez‐Luengo, Miguel Ángel; Rovira, Miguel; Serrano, Manuel; Fernandez‐Marcos, Pablo Jose; Martinez, Lola
Abstract: Flow cytometry is a powerful multiparametric technology, widely used for the identification, quantification, and isolation of defined populations of cells based on the expression of target proteins. It also allows for the use of surrogate reporters, either enzymatic or fluorescent, to indirectly monitor the expression of these target proteins. In this work, we optimised the dissociation protocol for the detection of the enzymatic reporter LacZ using the FACS‐Gal detection system with the fluorogenic substrate FDG to compare cis‐ versus trans‐positioned reporters efficiency. Particularly, for the FACS‐Gal optimization, we studied lung and haematopoietic tissues, focusing on cell recovery, viability, FDG loading conditions and distribution of cellular populations. Reporter genes such as LacZ can be placed together with the gene of interest in the same polycistronic mRNA (in cis), or in independent alleles (in trans), which can strongly affect the correlation with the reporter readout. To address this issue, we generated a mouse model containing both types of reporters for the same gene, and compared them. Our results clearly indicate that trans‐positioned reporters can be misleading, and that using a reporter gene in cis rather than trans is a much more specific method to sort for cells undergoing Cre‐mediated recombination. © 2017 International Society for Advancement of Cytometry